(untitled) (BIRDEM Medical Journal, 2017)
A 7-year-old boy was referred to the department of conservative dentistry and endodontics, Bangabandhu Sheikh Mujib Medial University (BSMMU) with pain on his left lower jaw. After clinical and radiological examination, it was diagnosed as a case of reversible pulpitis. Biodentine pulpotomy was performed followed by permanent restoration with glass-ionomer. The presented case was done to evaluate the efficacy of Biodentine as pulpotomy medicament in primary molar teeth, on follow-up it was found to be successful. Birdem Med J 2017; 7(3): 238-241